INTERCONNECTION MODEL OF MORALS-REASONING-RESEARCH IN PESANTREN CURRICULUM - Kuswandi, Iwan; Tobroni, Tobroni; In'am, Akhsanul; Khozin, Khozin; Asmoni, Asmoni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This paper described the interconnection model of morals-reasoning-research in the curriculum of Tarbiyatul Muallimien al-Islamiyah (known as TMI) Al-Amien Prenduan. It also examined the supporting and inhibiting factors for the implementation of the interconnected-curriculum. It is a case study employing observation, interviews and documentation, and the data were analyzed using qualitative analysis. Two conclusions were drawn. First, TMI uses multidisciplinary approaches in its curriculum by interconnecting morals, reason and research. Morals are instilled through reading and learning the morals books such as Ta‘lîm al-Muta‘allim and Iḥyâ’ ‘Ulûm al-Dîn. The reasoning skills are taught through school subjects such as logic, Islamic jurisprudence and the science of hadith. In contrast, the research skills are taught through research subjects and a compulsory program called writing a research paper. Second, the class classification model, which takes students’ talent and interest into account, and other research-related programs such as book review and fatḥ al-kutub (classical book research) are the supporting factors for the writing program. They are accommodating for students in completing their writing. Meanwhile, there are also numbers of inhibiting factors such as student’s lacking motivation, the prohibition of internet use, unsuitable supervisor expertise, and the minimum role of Islamic Study Center (Pusdilam).